(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper is an exploration of the buying behavior of consumers while shopping online. The Internet has transformed the way people shop and it is considered as an effective tool for business transactions. Internet access has become a necessity for everyone just like food, water, air, shelter, education etc. More and more people prefer online stores over brickandmortar stores due to numerous advantages. Customers conduct in-depth research about the products online before approaching a salesperson. Convenience and time saving are the two most important factors which persuades the customers to shop online. Customers also get the advantage of comparing the prices of different products. The most important aspect of online shopping is that customers get the option to purchase at any time of the day as online shopping sites are available 24/7.This study aims at determining the various factors affecting the buying behavior of consumers while shopping online.